2021
DOI: 10.3390/biology10121237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olive Cake and Cactus Cladodes Incorporation in Goat Kids’ Diet on the Rumen Microbial Community Profile and Meat Fatty Acid Composition

Abstract: The olive cake (OC) and the cactus cladodes (CC) are two alternative feed resources widely available in the southern Mediterranean region that could be used in ruminants’ diet. Their impact on the rumen bacterial ecosystem is unknown. This work aims to evaluate their effects on the microbial community and meat fatty acids of goat’s kids. Forty-four goat kids were divided into four groups receiving diets with conventional concentrate, or 35% OC, or 30% CC, or 15% OC, and 15% CC. After 3 months, these animals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Their lactation lasts 120 days, averaging 0.504 kg/goat. In addition, this breed shows excellent tolerance to diseases [3]. Published works about this indigenous goat have only explored the aspects related to its genetic characteristics [4] and the effect of alternative feed resources' incorporation on goat meat and milk production [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Their lactation lasts 120 days, averaging 0.504 kg/goat. In addition, this breed shows excellent tolerance to diseases [3]. Published works about this indigenous goat have only explored the aspects related to its genetic characteristics [4] and the effect of alternative feed resources' incorporation on goat meat and milk production [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the spread of its use as integrator in animal feeding is mainly related to the presence of substances with antioxidant and radical scavenging activity, and to its richness in monounsaturated fatty acids (MUFAs) (Ghanbari et al, 2012). There are many studies on the incorporation of this by-product in livestock diet, for example in broilers (Al-Harthi, 2016), pigs (Joven et al, 2014;Liotta et al, 2019), goats (Alkhtib et al, 2021;El Otmani et al, 2021), sheep Chiofalo et al, 2004;Vargas-Bello-Pérez et al, 2013, dairy cattle (Zilio et al, 2015Neofytou et al, 2020), and beef cattle (Estaún et al, 2014;Branciari et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, the mean community alpha‐diversity indexes including ACE, Chao 1, Shannon and phylogenetic diversity (PD)‐while‐tree indexes (Willis, 2019 ) were significantly elevated in faecal samples of mice treated with EV LV compared to untreated controls (Figure 6b ), confirming expanded richness and diversity of the bacterial community in faecal microbiota of EV LV ‐treated mice. The principal component analysis (PCA) and non‐metric multidimensional‐scaling (NMDS) with PERMANOVA analysis ( R 2 = 0.620, p = 0.002) (El Otmani et al., 2021 ; Gui et al., 2021 ) showed that the microbiota composition of mice treated with EV LV partially overlapped with the normal group, whereas a significant separation was found between normal and untreated control groups (Figure 6c ), demonstrating the modulatory effects of EV LV on microbiota. Examination of the relative abundance of different bacterial phylum revealed that symbiotic bacteria Bacteroidota represented by Allistipes and Odoribacter species and Verrucomicrobia ( Akkermansia ) (Cheng et al., 2023 ) were dramatically restored (Figure 6d–f ), whereas pathogenic Proteobacteria and Firmicutes (Rizzatti et al., 2017 ), exemplified by Desulfovibrionaceae bacterium (Rowan et al., 2010 ) and Escherichia‐Shigella species, one of bacteria primarily targeted by LL37 (Xhindoli et al., 2016 ), or Turcibacter and Erysipelatoclostridium (Cheng et al., 2023 ) significantly decreased in faeces of EV LV ‐treated mice compared to untreated controls (Figure 6d–f ), suggesting that EV LV restore the diversity and balance of microbiota by enriching commensal bacteria and inhibiting pro‐inflammatory bacteria in the gut of mice with chronic UC.…”
Section: Resultsmentioning
confidence: 99%